Pengaruh Komunikasi Pimpinan dan Bawahan Terhadap Kinerja Karyawan Restoran Ayam Bawang Cak Per Cabang Malang - Slamet, Slamet; Imami, Nor Ali Sukkron (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2020)
This research aims to understand: 1) The communication intensity level at Ayam Bawang Cak Per Restaurant, Malang Branch; 2) The employee performance at Ayam Bawang Cak Per Restaurant, Malang Branch; and 3) To know the communication influence between branch managers to employees on employee performance at Ayam Bawang Cak Per Restaurant, Malang Branch. This research used quantitative methods in the process and consist of two variables, dependent and independent. Communication is the independent variable and employee performance is the dependent variable. The research sample was taken 99% of the total population 50 people. Sampling in the study using the population sample method. Where in this case the researcher made the entire population as the research sample.The result showed that: 1) The communication intensity level between branch managers and subordinates was at a moderate level with a percentage of 75% of 30 employees; 2) The employee performance level was at the medium category with a percentage of 65% of 24 employees; and 3) There is a significant influence between communication on employee performance at Ayam Bawang Cak Per Restaurant, Malang Branch.The effective contribution or predictive power is shown by a coefficient (R2) of 0.256, which means that communication has an effect of 25.6% on employee performance, and the rest is due to variables not mentioned in this study